Factors Affecting the Income of Palm Sugar SMEs in Kaidipang District, North Bolaang Mongondow Regency - Delya Yustika Buhang; Sri Endang Saleh; Sri Indriyani Dai (Gorontalo State University, 2022)
This study aims to determine the factors that influence the income of palm sugar SMEs in Kaidipang District, North Bolaang Mongondow Regency. This type of research is survey research. Survey research is research that takes a sample from one population and uses a questionnaire as the main data collection tool. The types of data used in this research are primary data and secondary data. primary data is data obtained directly from the first source of the field in the form of data obtained through interviews. The results of the study show that capital has a positive but not significant effect on the income of SMEs. Capital has a positive effect on the income of SMEs. The number of workers has a positive and significant effect on the income of SMEs in North Bolaang Mongondow district. Raw materials have a positive but not significant effect on MSME income. The level of education has a negative effect on the income of palm sugar SMEs. Technology has a positive but not significant effect on the income of palm sugar SMEs. MSME Income = 4.739 + 0.065 Capital + 0.298 Total Labor + 0.132 Raw Materials - 0.079 Education Level + 0.162 Technology + e